Practice Patterns of Treatment Strategy of Limited-Stage Small-Cell Lung Cancer: Survey of Chinese Oncologists - Xu, Chang; Li, Meng; Cai, Xuwei; Yuan, Shuanghu; Cao, Jianzhong; Zhu, Shuchai; Chen, Ming; Bi, Nan; Hu, Xiao; Li, Jiancheng; Zhou, Wei; Wang, Ping; et al. (Frontiers in Oncology, 2022)
Background: Thoracic radiotherapy (TRT) with concurrent chemotherapy is the standard treatment of limited-stage small-cell lung cancer (LS-SCLC). However, there is still a controversy surrounding the treatment strategy especially optimal dosing and fractionation schedule. Current practice patterns among Chinese oncologists are unknown. Materials and Methods: We surveyed 212 Chinese oncologists using a questionnaire including 50 questions designed by experienced oncologists. Questions covered demographic data, treatment recommendations, and self-assessed knowledge of guidelines or key clinical trials for SCLC. The Chi-square test and Fisher’s exact test were utilized to describe the result of the study. Results: The response rate was 97% (207/212). Of all the respondents, 69% preferred TRT QD, 29% preferred BID, and 2% chose HFRT. For those who prefer TRT QD, 72% preferred a total dose of 60Gy, followed by 15% opting for 66Gy, 12% for<60Gy, and 1% for 70Gy. Of those who prefer BID, 79% preferred a total dose of 45Gy, with 4% choosing 30Gy, 8% choosing 50Gy, 7% choosing 54Gy, and 2% choosing>54Gy. Regarding PCI, 82% of participants believed that PCI should be performed when treatment completed and 13% believed that PCI should begin immediately after concurrent chemoradiotherapy. As for other therapies, 26% of participants choose concurrent anti-angiogenic therapy during SCLC treatment, and 49% of which recommended small-molecule TKI as the main anti-angiogenic therapy. Conclusion: Substantial variation exists in how Chinese oncologists approach TRT dosing and fractionation for LS-SCLC. Almost 70% of respondents reported administering TRT QD more often in daily work. The most common doses were 60Gy QD and 45Gy BID.